2004
DOI: 10.1002/chem.200304827
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Applications in Radical/Radical Cationic Cascade Reactions

Abstract: Oxidative photoinduced electron transfer (PET) reactions have been performed with various cyclic cyclopropyl(vinyl) silyl ethers bearing an olefinic or acetylenic side chain. The reactions result in bi- to tetracyclic ring systems via a fragmentation-radical/radical cationic addition reaction pathway with well defined ring juncture. The mode of cyclisation (endo/exo) can be partially controlled by addition of nucleophiles due to the suppression of radical cationic reaction pathways. Quantum chemical calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 50 publications
(25 reference statements)
1
26
0
Order By: Relevance
“…[14] Obviously the OTMS group has a more profound influence on the electronic structure of the cyclopropane radical cation than the phenyl group, as cyclopropyl silyl ethers undergo a multitude of radical cationic fragmentation, addition and rearrangement reactions. [16][17][18][19] Calculations on the model compound, 1-methoxy-1,2-dimethylcyclopropane 3, show that the strong distortions on ionization persist even if the OTMS group is replaced by an OMe group (but 3 a is 6.3 kcal mol À1 more stable than 3 b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[14] Obviously the OTMS group has a more profound influence on the electronic structure of the cyclopropane radical cation than the phenyl group, as cyclopropyl silyl ethers undergo a multitude of radical cationic fragmentation, addition and rearrangement reactions. [16][17][18][19] Calculations on the model compound, 1-methoxy-1,2-dimethylcyclopropane 3, show that the strong distortions on ionization persist even if the OTMS group is replaced by an OMe group (but 3 a is 6.3 kcal mol À1 more stable than 3 b).…”
Section: Resultsmentioning
confidence: 99%
“…[1,2,10] The nucleophilic ring opening of cyclopropyl radical cations under PET conditions, which takes place under inversion of the carbon center which is attacked by the nucleophile (Scheme 1), has been studied mainly by the group of Dinnocenzo. [11][12][13][14] In contrast to these results, we found that cyclopropyl silyl ethers undergo spontaneous fragmentation, sometimes followed by re-cyclisation to form new products, in absence of nucleophiles, [17][18][19] that is, under conditions where alkyl-or aryl-substituted cylopropanes do not even epimerize. [10] In cyclic systems intermolecular addition reactions lead predominately to the endo-addition products, which is caused by the selectivity of initial fragmentation (Scheme 2).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Starting materials and solvents were purified using standard laboratory techniques. [62] 3-(1-Cyclohexenylethyl)-2-cyclohexen-1-one (18): tert-Butyllithium (10.0 mL, 17.0 mmol of a 1.7  solution in pentane) was added to a solution of 2,2Ј-bipyridine (2 mg) in dry THF (80 mL) cooled to Ϫ78°C and then a solution of 1-iodo-2-(1-cyclohexenyl)ethane 19 [32][63] (1.75 g, 7.42 mmol) in dry THF (10 mL) was added dropwise. The reaction mixture was stirred for 1.5 h at Ϫ78°C before a solution of 3-ethoxycyclohex-2-enone 21 (1.00 g, 7.13 mmol) in dry THF (10 mL) was added dropwise.…”
Section: Experimental Section General Remarksmentioning
confidence: 99%